Assessing the Suitability of Kisumu County for O. niloticus Culture Based on Water Availability Criteria using Free GIS and SMCE Software - Mokoro, A. K.; Njiru, J.; Matolla, G. (Africa Environmental Review Journal, 2022)
Aquaculture productivity in Kenya is lower than the level required to support major section development despite an escalated need for fish. Low fish productivity is due to the location of fish ponds without considering site suitability. Aquaculture scientists have identified specific suitability criteria namely water availability as important for fish pond location. There is therefore need to generate a water availability suitability map that can guide location of fish ponds to enable maximization of production. This study used free GIS and SMCE software to generate a water availability suitability map for O.niloticus culture in Kisumu County. The basis was evolved and regulated through classification, weighting and combination of four sub-criteria (size of watershed, amount of annual rainfall, rate of evaporation and rate of seepage). Each sub-criterion was classified into a four-level land suitability assessment scale based on FAO weighted scores, weighted by a team of experts using AHP pairwise comparison matrix and converted to a map layer. Weighted linear combination using SMCE was utilized to develop O.niloticus suitability map. Verification of results was done through comparison of fish production in various suitable sites by interviews with aquaculture farmers and fisheries officers. The findings revealed that nearly 65.5% of Kisumu County is highly suitable, 23.02% is suitable and the remaining 11.46% was not suitable for pond farming of O.niloticus.